2020
DOI: 10.3390/cryst10090718
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Carbon: An Update on Graphene’s Dermal, Inhalation, and Gene Toxicity

Abstract: Recent studies on gene, inhalation and dermal toxicity of few-layer graphene have revealed much lower health risk than expected. This could pave the way for graphene as a young member of the nanocarbons family to become the “heir presumptive” to the long-reigning carbon black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In particular, it has been observed that the protection efficiency of carbon black decreases with increasing particle size, with the best performance achieved with particles < 20 nm [59]. A limitation associated with the use of carbon black is related to its manufacturing process, associated with environmental and health issues, since it implies partial combustion of fossil fuels and generation of greenhouse gas byproducts and polycyclic hydrocarbons [7,23]. Carbon nanotubes (CNT) are another example of carbon-based materials that have shown a photostabilizing effect in polymer matrices.…”
Section: Mechanisms Of Actions Of Photostabilizersmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it has been observed that the protection efficiency of carbon black decreases with increasing particle size, with the best performance achieved with particles < 20 nm [59]. A limitation associated with the use of carbon black is related to its manufacturing process, associated with environmental and health issues, since it implies partial combustion of fossil fuels and generation of greenhouse gas byproducts and polycyclic hydrocarbons [7,23]. Carbon nanotubes (CNT) are another example of carbon-based materials that have shown a photostabilizing effect in polymer matrices.…”
Section: Mechanisms Of Actions Of Photostabilizersmentioning
confidence: 99%
“…The latter is most suitable for bulk industrial applications, such as UV protection, due to its ease of manufacturing and costeffectiveness. Commercial-grade, also known as few-layer graphene, is typically made of five to ten atomic layers of sp 2 -hybridized sheets of carbon and can be prepared through a sustainable process based on mechanochemical exfoliation of graphite [17,23,73]. Furthermore, it has been demonstrated recently that few-layer graphene is rather a safer alternative to conventional UV additives [6,7,23,[46][47][48].…”
Section: Types Of Graphenementioning
confidence: 99%
See 2 more Smart Citations
“…For instance, GNP-filled polymers showed improved mechanical [6], electrical [7], gas barrier [8] and heat conduction [9] properties. Moreover, recent studies on the gene toxicity of GNP have concluded that graphene is much safer than carbon black for large-scale use [10]. However, the study of the GNP/glass fiber/polymer ternary composites is limited in the literature.…”
Section: Introductionmentioning
confidence: 99%